Articular Cartilage Surface Topography and Roughness in Frozen Tissue Samples Using Optical Coherence Microscopy - Abbass, Sadiq Jafer (Nahrain University College of Engineering Journal, 2017)
This paper describes a method to visualize the topography of the surface of cartilage. Optical Coherence Microscopy (OCM) technique has been used to get two dimensional images of frozen tissue samples of bovine articular cartilage. Optical Coherence Microscopy (OCM) is a combination of optical coherence tomography and confocal microscopy. Coherence gate from OCT and confocal gate from confocal microscopy can achieve higher resolution and deeper penetration depth. The precise three-dimensional topography of the cartilage surfaces has been obtained. The full-image roughness, for frozen samples has been obtained.